Consolidation of a High Plasticity Dredged Marine Clay Incorporating Single Drainage Path With Granular Geowastes - Siti Farhanah, SM Johan; Chan, Chee Ming; Tan, Poi Cheong; Mohammad Zawawi, Rosman (Semarak Ilmu Publishing, 2024)
The present study simulated a dredged marine clay backfill in standard oedometers, where the examination was carried out on a consolidation process with a single drainage path using pavement milling waste and palm oil clinker. It was found that the dissipation of excess pore water from the soil increased with the thickness of the drainage layer, which facilitated a more effective drainage rate. Also, palm oil clinker was observed to be prone to crushing at higher applied stresses, leading to possible clogging of the pores and diminishing consolidation rate. However, the samples’ settlements were not observed to be particularly influenced by the drainage material used. Overall, both by-product wastes could be potentially reused as a drainage layer for field backfilling of dredged marine clay in the preloading stage, simultaneously introducing second lives to the waste materials in beneficial civil engineering applications.